Sexually dimorphic effects of prenatal diazepam exposure on respiratory control and the monoaminergic system of neonate and young rats - da Silva Junior, Carlos Aparecido [UNESP]; Patrone, Luís Gustavo A. [UNESP]; Biancardi, Vivian; Vilela-Costa, Heloísa H.; Marques, Danuzia A.; Cristina-Silva, Caroline [UNESP]; da Costa Silva, Kaoma Stephani; Bícego, Kênia C. [UNESP]; Szawka, Raphael E.; Gargaglioni, Luciane H. [UNESP] (Springer Nature, 2022)
Pregnancy is highly affected by anxiety disorders, which may be treated with benzodiazepines, especially diazepam (DZP), that can cross the placental barrier and interact with the fetal GABAergic system. We tested whether prenatal exposure to DZP promotes sex-specific postnatal changes in the respiratory control of rats. We evaluated ventilation (VE˙) and oxygen consumption (V ˙ O2) in resting conditions and under hypercapnia (7% CO2) and hypoxia (10% O2) in newborn [postnatal day (P) 0–1 and P12–13)] and young (P21–22) rats from mothers treated with DZP during pregnancy. We also analyzed brainstem monoamines at the same ages. DZP exposure had minimal effects on room air–breathing variables in females, but caused hypoventilation (drop in VE˙ /V ˙ O2) in P12–13 males, lasting until P21–22. The hypercapnic ventilatory response was attenuated in P0–1 and P12–13 DZP-treated females mainly by a decrease in tidal volume (VT), whereas males had a reduction in respiratory frequency (fR) at P12–13. Minor changes were observed in hypoxia, but an attenuation in V˙ E was seen in P12–13 males. In the female brainstem, DZP increased dopamine concentration and decreased 5-hydroxyindole-3-acetic acid (5-HIAA) and the 3,4-dihydroxyphenylacetic acid (DOPAC)/dopamine ratio at P0–1, and reduced DOPAC concentration at P12–13. In males, DZP decreased brainstem noradrenaline at P0–1. Our results demonstrate that prenatal DZP exposure reduces CO2 chemoreflex only in postnatal females and does not affect hypoxia-induced hyperventilation in both sexes. In addition, prenatal DZP alters brainstem monoamine concentrations throughout development differently in male and female rats.
Keywords: Benzodiazepine; Breathing; Chemosensitivity; Development; GABA